Gambaran Profil Hematologi Rutin Pasien TB Paru Sebelum dan Sesudah Pengobatan dengan Obat Antituberkulosis - Sitanggang, Ervina Julien; Sihombing, Jenny Ria (Nommensen Journal of Medicine, 2023)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (M.tb) which often attacks the lung parenchyma and can also attack other organs. Changes can be found in the hematological profile of TB patients both at the time of diagnosis and after treatment. Objective: This study was conducted to obtain routine hematological profiles of pulmonary TB patients before and after treatment with anti-tuberculosis drugs for 3 months, 4 months, and 5 months. Methods: This study was an observational descriptive study. The population in this study was pulmonary TB patients at Martha Friska Hospital and Hermina Medan Hospital for the period October 2021-August 2022. The samples in this study were taken from medical record data of all pulmonary TB patients at Martha Friska Hospital and Hermina Medan Hospital for the period of October 2021-August 2022 (total sampling). Results: In this study, 39 research subjects were obtained, age range of 15-79 years. Before treatment, the majority of patients had anemia (76.92%), leukocytosis (61.54%), normal platelets (66.67%), and elevated ESR (53.85%). After 3 months of treatment, anemia was experienced by 30%, leukocytosis by 0%, normal platelets by 80%, and elevated ESR by 20% of patients. After 4 months of treatment, anemia was experienced by 52.17%, leukocytosis by 4.35%, normal platelets by 65.22%, and elevated ESR by 4.35% of patients. After 5 months of treatment, anemia was experienced by 50%, leukocytosis by 0%, platelets normal by 83.33%, and elevated ESR by 0% of patients. Conclusion: The majority of patients develop anemia, leukocytosis, and elevated ESR before treatment with antituberculosis drugs. There was a decrease in the proportion of patients who developed anemia, leukocytosis, and an elevated ESR after treatment with antituberculosis drugs for 3 months, 4 months, and 5 months.